Pentingnya Pendidikan Kewarganegaraan Untuk Membangun Moral Anak Bangsa di Era Globalisasi Kota Jayapura - Marthen Timisela; Nimrod Baab (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2021)
Civic education plays an important role in shaping the morals and character of the nation's children, especially in the midst of the increasingly strong current of globalization. This article aims to explore the importance of civic education in the context of Jayapura City, by emphasizing the moral and ethical aspects that need to be instilled in the younger generation. Through literature review and data analysis, this article seeks to provide insight into how civic education can be a tool for building the morals of the nation's children in the era of globalization.